Transnationalism in the Australian Curriculum: new horizons or destinations of the past?. Issue 3 (3rd May 2016) - Casinader, Niranjan
Abstract : Educationally, it is arguable that transnationalism has been primarily framed around course delivery by educational institutions within international contexts. However, it is a more complex notion, incorporating ideas such as global citizenship and intercultural understanding. Consequently, if the Australian Curriculum is the national substantiation of Australia's educational priorities, designed to prepare young Australians for a globalised future, it should reflect such transnationalist elements. This paper contends that, despite contrary impressions, the Australian Curriculum is more of a protective reinforcement of older conceptions of a 'Western' community than one centred on forward-looking global principles. Its codifications dominate at the cost of acknowledging other points of reference that represent a collective transnational sensibility, and thus it embodies a lost national opportunity. Recent criticisms that the Australian Curriculum fails to adequately reflect 'Western' civilisation are ill-founded, as they ignore the strong presence of 'Western' intellectual constructs throughout the Australian Curriculum's design and content.